Advancing Non-Contact Vital Sign Measurement using Synthetic Avatars - McDuff, Daniel; Hernandez, Javier; Wood, Erroll; Liu, Xin; Baltrusaitis, Tadas (ArXiv, 2020)
Non-contact physiological measurement has the potential to provide low-cost, non-invasive health monitoring. However, machine vision approaches are often limited by the availability and diversity of annotated video datasets resulting in poor generalization to complex real-life conditions. To address these challenges, this work proposes the use of synthetic avatars that display facial blood flow changes and allow for systematic generation of samples under a wide variety of conditions. Our results show that training on both simulated and real video data can lead to performance gains under challenging conditions. We show state-of-the-art performance on three large benchmark datasets and improved robustness to skin type and motion.